Method for improving wear resistance of bearing
By preparing the Cr transition layer and HfO2/WS2 composite coating on the bearing surface, the problem of insufficient wear resistance of bearings under dry operation conditions is solved, high-performance operation of bearings is achieved, friction loss and wear are reduced, and application scope is expanded.
Patent Information
- Application Number
- CN202510485451.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-17
- Publication Date
- 2025-07-18
AI Technical Summary
The existing bearings have insufficient wear resistance under dry operation conditions. Traditional coatings are difficult to meet the demanding requirements of modern industry under high temperature, high speed and high load conditions, and there are problems such as poor coating bonding, easy cracking, high preparation cost and compatibility.
The Cr transition layer and HfO2/WS2 composite coating were prepared on the bearing surface. Through the non-equilibrium magnetron sputtering technology, the sputtering parameters are regulated to form a dense HfO2/WS2 composite coating, which enhances the hardness and bonding force of the coating and reduces the friction coefficient.
Significantly improve the tribological performance of bearings, extend service life, reduce equipment maintenance costs, and is suitable for a variety of industrial scenarios to meet high-performance requirements.
Smart Images

Figure CN120330665A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of bearing surface engineering, in particular to a method for improving the wear resistance of a bearing. Background Art
[0002] In the modern industrial production system, bearings are the core basic components of various mechanical equipment, and their performance is directly related to the overall operation status, reliability and service life of the equipment. Among the many performance indicators of bearings, wear resistance occupies a pivotal position in practical applications, especially under dry running conditions, wear resistance has become a key factor in determining whether the bearing can work stably.
[0003] Dry running means that the bearing lacks effective protection from lubricating media during operation, and the friction pair surfaces are in direct contact and interact with each other. Under such harsh working conditions, the bearing faces huge challenges. Without the intervention of lubricating media, the friction coefficient will increase significantly, resulting in a large amount of friction heat being generated rapidly. At the same time, the heat is difficult to dissipate, causing the bearing temperature to rise sharply. Excessive temperature will cause a series of problems, such as reduced hardness of bearing materials and changes in organizational structure, which will accelerate the wear process of the bearing surface. In addition, the lack of lubricating media also makes it easier for various wear forms such as surface fatigue wear, adhesive wear and abrasive wear to occur. In severe cases, it will cause the bearing to lose precision, generate abnormal noise, or even get stuck directly, making the equipment unable to operate normally.
[0004] At present, in order to improve the wear resistance of bearings under dry running conditions, preparing coatings on the bearing surface has become an important technical means. Common coating types include metal coatings, ceramic coatings, carbon-based coatings, and various composite coatings.
[0005] Metal coatings, such as chrome plating, can reduce the wear of bearing surfaces to a certain extent due to their hardness. However, metal coatings have obvious limitations. Under high temperature conditions, the metal structure will change, the hardness will decrease, and its wear resistance will be greatly reduced; when subjected to high loads, metal coatings are prone to plastic deformation and cannot continue to effectively protect the bearing surface.
[0006] Ceramic coatings have the characteristics of high hardness and high melting point, which can theoretically provide good wear protection for bearings. However, ceramic materials themselves have poor toughness. When subjected to impact loads, the coating is very likely to crack. Once cracks appear, they will gradually expand and eventually cause the coating to peel off, which will not only lose its protective function, but the peeling fragments may also aggravate the wear of the bearing.
[0007] Carbon-based coatings, such as diamond-like carbon coatings (DLC), have the advantage of a low coefficient of friction and can reduce the frictional losses of bearings to a certain extent. However, the preparation process of DLC coatings is complex, with high requirements for equipment and technology, resulting in high preparation costs and limiting their large-scale application. Moreover, the bonding force problem between DLC coatings and bearing substrate materials has not been well solved. Under long-term friction and vibration, the coatings are prone to peeling off from the substrate, affecting the stable performance of their wear resistance.
[0008] Various composite coatings attempt to integrate the advantages of multiple materials to achieve better wear resistance. However, in the actual preparation and application process, many problems are faced. It is difficult to ensure the compatibility between different materials, which easily leads to stress concentration inside the coatings and reduces the overall performance of the coatings; the interfacial bonding strength is insufficient, causing delamination of the coatings during use and unable to fully exert the synergistic advantages of the composite coatings.
[0009] With the continuous development of modern industry towards high speed, high precision, and high load, the requirements for the wear resistance of bearings are becoming increasingly stringent. In the aerospace field, the bearings in aircraft engines need to operate continuously and stably under extreme conditions of high temperature, high speed, and high load. Existing coating technologies are difficult to meet such demanding wear resistance requirements; in the field of electronic devices, such as the bearings in micro-motors, due to their small size, extremely high requirements for wear resistance and precision are imposed, and traditional coating technologies are also difficult to achieve ideal effects. Therefore, it is urgent to develop a new method that can effectively overcome the shortcomings of existing coatings and significantly improve the wear resistance of bearings under dry running conditions, which has important practical significance for promoting the progress of industrial technology, improving production efficiency, and reducing equipment maintenance costs. Summary of the Invention
[0010] To solve the deficiencies in the prior art, the present invention provides a method for improving the wear resistance of bearings. By preparing a Cr transition layer and a HfO2 / WS2 composite coating on the surface of the bearings, the tribological performance of the bearings under dry running conditions is significantly improved, the degree of wear is reduced, and the service life of the bearings is extended to meet the high-performance requirements of modern industry for bearings.
[0011] To achieve the above objective, the specific scheme adopted by the present invention is as follows: A method for improving the wear resistance of bearings mainly includes the following steps: S1. Clean the bearings; S2. Fix the bearings on the substrate stage in the vacuum chamber; S3. Place the Cr target and the WS2 target on different DC target positions respectively, and place the HfO2 target on the RF target position. Adjust the angles of the targets relative to the center line perpendicular to the substrate stage and the vertical distances between the targets and the substrate stage; S4. First, evacuate the vacuum chamber. During the evacuation process, heat the bearing synchronously, and the maximum heating temperature is 300 °C. When the vacuum degree reaches 5e-4 Pa, introduce the working gas argon, with an argon flow rate of 20 - 50 sccm, control the deposition pressure to be 0.5 - 1.8 Pa, turn on the power supply of the Cr target, and perform thin film sputtering on the bearing surface to form a Cr transition layer on the bearing surface. S5. Adjust the argon flow rate to 40 - 60 sccm and the deposition pressure to 0.8 - 1.2 Pa. Then, turn on the power supplies of the WS2 target and the HfO2 target simultaneously, and perform co-sputtering on the surface of the Cr transition layer to form an HfO2 / WS2 composite coating on the surface of the Cr transition layer. Then, let it cool naturally.
[0012] Further, in step S1, place the bearing in absolute ethanol and ultrasonically clean it for 15 minutes, then ultrasonically clean it with acetone for 15 minutes, and finally dry it.
[0013] Further, in step S3, the purity of the WS2 target is 99.99%; the purity of the HfO2 target is 99.99%.
[0014] Further, in step S4, when preparing the Cr transition layer, the sputtering power is 50 - 80 W, and the sputtering time is 15 - 20 minutes.
[0015] Further, in step S5, when preparing the HfO2 / WS2 composite coating, the power for radio frequency sputtering of HfO2 is 40 - 100 W, the power for direct current sputtering of WS2 is 150 W, and the sputtering time is 90 - 100 minutes.
[0016] Beneficial effects:
[0017] (1) Coating preparation process advantages and performance improvement: The present invention uses unbalanced magnetron sputtering technology to successfully prepare an HfO2 / WS2 composite coating. By precisely controlling the coating process parameters (such as target sputtering power, gas flow rate, vacuum degree, etc.), an HfO2 / WS2 composite coating under the optimal power can be obtained. The unbalanced magnetron sputtering technology can enhance the energy and activity of sputtered particles, promote the uniform deposition of HfO2 and WS2 particles on the bearing surface, and form a dense and excellent-performance coating structure. Under dry running conditions, this structure can significantly improve the tribological performance of the bearing, effectively reduce the friction coefficient, reduce wear, extend the service life of the bearing, ensure its operation stability, and meet the high-performance requirements of the industry for dry running bearings.
[0018] (2) Excellent performance given by high crystal strength: The WS2-doped HfO2 composite coating has high crystal strength, which brings excellent mechanical properties. The coating hardness is 5.5-9.2GPa, the elastic modulus is 75-109GPa, and the H / E value is between 0.073-0.79. The appropriate H / E value enables the coating to resist wear by hardness when subjected to force, and to rely on elasticity to buffer stress and prevent brittle fracture. Under optimal sputtering power, the average friction coefficient of the coating is as low as 0.062, which reduces friction resistance and energy loss during operation, reduces heat load, and comprehensively exhibits excellent tribological properties.
[0019] (3) Significant advantages over pure WS2 coating: Under the optimal parameters, the hardness of pure WS2 coating is only 0.084GPa, and the friction coefficient is 0.092. In comparison, the friction coefficient of HfO2 / WS2 composite coating is further reduced, reaching an average of 0.062, and the wear volume is also significantly reduced. HfO2 enhances the hardness and structural stability of the coating, and synergizes with WS2 to effectively support the coating and prevent WS2 from excessive wear, further improving the tribological performance, extending the service life of the bearing, reducing equipment maintenance costs, and improving the economic benefits of industrial production.
[0020] (4) Process controllability and wide applicability: In the present invention, the composite coating with optimal performance is prepared by adjusting the coating process parameters, and this process has good controllability and repeatability. Different bearing application scenarios and working conditions can achieve customized coating preparation by adjusting the process parameters. Whether it is precision instrument bearings with extremely high requirements for friction coefficient, or heavy machinery bearings with strict requirements for wear resistance, HfO2 / WS2 composite coatings that meet their specific needs can be prepared by optimizing the process parameters. This wide applicability enables the technology of the present invention to be applied in multiple industrial fields, greatly expanding its scope of application and improving the practical value of the technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a wear scar morphology diagram of the product obtained in Example 1 after the friction and wear test.
[0022] Figure 2 This is a wear scar morphology diagram of the product obtained in Example 2 after the friction and wear test.
[0023] Figure 3 This is a wear scar morphology diagram of the product obtained in Example 3 after the friction and wear test.
[0024] Figure 4 This is a wear scar morphology diagram of the product obtained in Example 4 after the friction and wear test.
[0025] Figure 5 This is a wear scar morphology diagram of the product obtained in Example 1 after the friction and wear test.
[0026] Figure 6 It is the morphology diagram of the wear scar after the friction and wear test on the product obtained in Comparative Example 2. Specific embodiments
[0027] The technical solutions of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without making creative efforts shall fall within the protection scope of the present invention.
[0028] The present invention provides a method for improving the wear resistance of bearings, mainly including the following steps: S1. Bearing cleaning: Place the bearing in anhydrous ethanol and ultrasonically clean it for 15 minutes, then ultrasonically clean it with acetone for 15 minutes, and finally dry it; anhydrous ethanol has good solubility and volatility, and can effectively dissolve and remove organic pollutants such as oil stains and greases on the bearing surface; during ultrasonic cleaning, the tiny bubbles generated by ultrasonic cavitation break on the bearing surface, generating a strong impact force, which can peel off stubborn dirt; acetone has a stronger solubility for organic pollutants, and further cleaning can ensure the complete removal of residual oil stains and impurities; the drying treatment can remove the surface moisture and avoid the influence of moisture on the bonding between the subsequent coating and the bearing substrate; this step provides a clean and dry surface for the subsequent coating preparation, ensures the tight bonding between the coating and the bearing, and prevents the coating from peeling off or the performance from decreasing due to surface impurities. S2. Fixing the bearing: Fix the cleaned bearing on the substrate stage in the vacuum chamber. A stable fixing method ensures the accurate position of the bearing during the subsequent sputtering process, avoiding movement or shaking. This helps to precisely control the deposition position and thickness of the coating, ensures uniform coverage of the coating on the bearing surface, improves the uniformity and consistency of the coating, and thus ensures the same wear resistance of all parts of the bearing, avoiding increased local wear due to uneven coating. S3. Target preparation and adjustment: Place the Cr target and WS2 target with a purity of 99.99% on different DC target positions respectively, and place the HfO2 target with a purity of 99.99% on the RF target position. Precisely adjust the angle of the target relative to the center line perpendicular to the substrate stage and the vertical distance between the target and the substrate stage; different targets require different sputtering methods (DC sputtering or RF sputtering), and appropriate target position settings are the basis for effective sputtering; adjusting the target angle and distance can control the flight trajectory and energy of the sputtered particles; an appropriate angle makes the particles evenly deposit on the bearing surface, avoiding excessive or insufficient local deposition; an appropriate distance can ensure that the particles have appropriate energy to reach the bearing surface, ensuring the quality and performance of the coating, such as the density and adhesion of the coating. S4. Preparation of Cr transition layer: First, evacuate the vacuum chamber. During the evacuation process, heat the bearing synchronously, and the maximum heating temperature is 300 °C. When the vacuum degree reaches 5e-4 Pa, introduce the working gas argon, with an argon flow rate of 20 - 50 sccm, control the deposition pressure to be 0.5 - 1.8 Pa, turn on the power supply of the Cr target, and perform thin-film sputtering on the bearing surface. The sputtering power is 50 - 80 W, and the sputtering time is 15 - 20 minutes to form a Cr transition layer with a thickness of 200 - 250 nm on the bearing surface. Heating can, on the one hand, remove oxygen in the bearing, reduce the generation of oxygen during the working process, and prevent it from affecting the coating quality. On the other hand, it can improve the atomic activity on the bearing surface, enhance the bonding force between the coating and the substrate, and thus improve the coating quality. Argon, as the working gas, provides a stable environment for sputtering. The Cr transition layer can improve the bonding performance between the bearing substrate and the subsequent composite coating. The Cr element has good affinity with the bearing substrate material, can form strong chemical bonds, and enhance the coating adhesion. At the same time, the chemical stability and certain hardness of Cr provide stable support for the composite coating, improve the overall performance, and enable the subsequent composite coating to play a better role; S5. Preparation of HfO2 / WS2 composite coating: Adjust the argon flow rate to 40 - 60 sccm, and the deposition pressure to 0.8 - 1.2 Pa. Then turn on the power supplies of the WS2 target and the HfO2 target simultaneously, and perform co-sputtering on the surface of the Cr transition layer. The power for RF sputtering of HfO2 is 40 - 100 W, and the power for DC sputtering of WS2 is 150 W. The sputtering time is 90 - 100 minutes to form a HfO2 / WS2 composite coating with a thickness of 1.5 - 2.3 μm on the surface of the Cr transition layer. Then let it cool naturally. WS2 has good anti-friction performance, and its layered structure can slip during friction, reducing the friction coefficient. HfO2 has high hardness, good chemical stability, and high temperature resistance, which can enhance the wear resistance and corrosion resistance of the composite coating. The coating formed by the combination of the two has both anti-friction and wear-resistant characteristics. Natural cooling makes the coating structure and performance stable, avoids the generation of internal stress caused by rapid cooling, ensures the quality and performance of the coating, and improves the wear resistance of the bearing under dry running conditions.
[0029] Example 1
[0030] This example provides a method for improving the wear resistance of bearings, mainly including the following steps: S1. Bearing cleaning: Place the bearing in absolute ethanol and perform ultrasonic cleaning for 15 minutes, then perform ultrasonic cleaning in acetone for 15 minutes, and finally dry it; S2. Fix the bearing: Fix the cleaned bearing on the substrate stage of the vacuum chamber to ensure its stability in subsequent operations; S3. Target preparation and adjustment: Place the Cr target and WS2 target with a purity of 99.99% on different DC target positions respectively, and place the HfO2 target with a purity of 99.99% on the RF target position. Precisely adjust the angle of the target relative to the center line perpendicular to the substrate table and the vertical distance between the target and the substrate table. S4. Preparation of Cr transition layer: Evacuate the vacuum chamber. During the evacuation process, heat the bearing to 300 °C synchronously. When the vacuum degree reaches 5e-4 Pa, introduce argon gas with a flow rate set at 30 sccm, control the deposition pressure at 0.6 Pa, turn on the power supply of the Cr target, and sputter for 15 minutes with a sputtering power of 60 W to form a 200-nm-thick Cr transition layer on the bearing surface. S5. Preparation of HfO2 / WS2 composite coating: Adjust the argon gas flow rate to 50 sccm to keep the deposition pressure at 1.0 Pa. At the same time, turn on the power supplies of the WS2 target and the HfO2 target. The power for DC sputtering of WS2 is 150 W, and the power for RF sputtering of HfO2 is 40 W. Sputter for 90 minutes to form a 1.5-μm-thick HfO2 / WS2 composite coating on the surface of the Cr transition layer, and finally cool it naturally.
[0031] After detection, the mass percentages of each element in the HfO2 / WS2 composite coating prepared in this example are: O 6.02%, S 16.15%, Fe 1.61%, Hf 1.94%, W 74.28%.
[0032] Example 2
[0033] The difference between Example 2 and Example 1 is: (1) The power for RF sputtering of HfO2 is 60 W, and the thickness of the HfO2 / WS2 composite coating is 1.8 μm.
[0034] After detection, the mass percentages of each element in the HfO2 / WS2 composite coating prepared in this example are: O 4.21%, S 14.67%, Fe 1.77%, Hf 6.38%, W 72.96%.
[0035] Example 3
[0036] The difference between Example 3 and Example 1 is: (1) The power for RF sputtering of HfO2 is 80 W, and the thickness of the HfO2 / WS2 composite coating is 2 μm.
[0037] After detection, the mass percentages of each element in the HfO2 / WS2 composite coating prepared in this example are: O 4.59%, S 13.97%, Fe 1.71%, Hf 9.10%, W 70.62%.
[0038] Example 4
[0039] Example 4 is different from Example 1 in that: (1) the power during radio frequency sputtering of HfO2 is 100 W, and the thickness of the HfO2 / WS2 composite coating is 2.3 μm.
[0040] Upon detection, the mass percentages of the respective elements in the HfO2 / WS2 composite coating prepared in this example are: O 4.95%, S 13.75%, Fe 1.68%, Hf 10.66%, and W 68.96%.
[0041] Comparative Example 1
[0042] Comparative Example 1 is different from Example 1 in that: in step S5, only the WS2 target was sputtered to obtain a WS2 coating.
[0043] Comparative Example 2
[0044] Comparative Example 2 is different from Example 1 in that: in step S5, only the HfO2 target was sputtered to obtain an HfO2 coating.
[0045] Next, the performance of the products obtained in Examples 1-4 and Comparative Examples 1-2 was tested. The coatings prepared by the above process method were subjected to relevant tests using a scanning electron microscope, a nanoindentation instrument, and a friction and wear testing machine. The test results are shown in Table 1.
[0046] Table 1 Performance test results of the bearings
[0047] By testing the performance of the bearings prepared in Examples 1-4 and Comparative Examples 1-2, it was found that their friction coefficient and wear rate were significantly reduced and their wear resistance was significantly improved under dry running conditions, verifying the effectiveness of the method of the present invention.
[0048] Figures 1-4 is the morphology diagram of the wear scar after the friction and wear test of the products obtained in Examples 1-4. As can be seen from the figure, when the sputtering power of hafnium oxide is 40 W, peeling and spalling phenomena occur at the edge of the wear scar of the composite coating, and the scratch is relatively obvious. As the sputtering power of hafnium oxide increases, this peeling and spalling phenomenon improves and the wear scar becomes shallower and shallower; when the sputtering power is 80 W, only slight coating spalling occurs at the wear scar; when the sputtering power is increased to 100 W, from Figure 4 it can be seen that the peeling and spalling phenomenon becomes more serious, and the coating at the wear scar has basically peeled off. It is analyzed that under the action of cyclic loading, the periodic application of external force causes microcracks to occur in the coating. When the crack extends to a certain length, it will peel off due to the stress applied by the steel ball. In contrast, the tribological performance of this composite coating reaches the best when the sputtering power of hafnium oxide is 80 W. Figures 5-6It is the wear scar morphology diagram after the friction and wear test on the products obtained in Comparative Examples 1-2. It can be seen from Figure 5 that although the wear rate of the pure WS2 coating is relatively good, it can be seen from its surface that the coating is composed of several particles piled up, and the overall compactness of the coating is poor, showing low hardness and elastic modulus. Therefore, when it is used on bearings, it will show poor load-bearing capacity. It can be seen from Figure 6 and Table 1 that the pure HfO2 coating has high hardness and shows high brittleness. Therefore, the coating peeling range is large and the tribological properties are poor. In summary, when the sputtering power of hafnium oxide is 80W, the composite coating shows the best tribological properties.
[0049] The above is only the preferred embodiment of the present invention, and it does not impose any form of limitation on the present invention. Any equivalent transformation or modification made according to the essence of the present invention should be covered within the protection scope of the present invention.
Claims
1. A method for improving the wear resistance of bearings, characterized in that, It mainly includes the following steps: S1. Clean the bearing; S2. Fix the bearing on the substrate stage in the vacuum chamber; S3. Place the Cr target and the WS2 target on different DC target positions respectively, place the HfO2 target on the RF target position, and adjust the angle of the target relative to the center line perpendicular to the substrate stage and the vertical distance between the target and the substrate stage; S4. First evacuate the vacuum chamber, and heat the bearing synchronously during the evacuation process. The maximum heating temperature is 300 °C; when the vacuum degree reaches 5e-4 Pa, introduce the working gas argon, the argon flow rate is 20 - 50 sccm, control the deposition pressure to be 0.5 - 1.8 Pa, turn on the power supply of the Cr target, and perform thin film sputtering on the bearing surface to form a Cr transition layer on the bearing surface; S5. Adjust the argon flow rate to 40 - 60 sccm, the deposition pressure to be 0.8 - 1.2 MPa, then turn on the power supplies of the WS2 target and the HfO2 target simultaneously, and perform co-sputtering on the surface of the Cr transition layer to form a HfO2 / WS2 composite coating on the surface of the Cr transition layer; then cool it naturally.
2. A method for improving the wear resistance of a bearing according to claim 1, characterized in that, In step S1, place the bearing in absolute ethanol and perform ultrasonic cleaning for 15 minutes, then perform ultrasonic cleaning with acetone for 15 minutes, and finally dry it.
3. A method for improving the wear resistance of a bearing according to claim 1, characterized in that, In step S3, the purity of the WS2 target is 99.99%; the purity of the HfO2 target is 99.99%.
4. A method for improving the wear resistance of a bearing according to claim 1, characterized in that, In step S4, when preparing the Cr transition layer, the sputtering power is 50 - 80 W, and the sputtering time is 15 - 20 minutes.
5. A method for improving the wear resistance of a bearing according to claim 1, characterized in that, In step S5, when preparing the HfO2 / WS2 composite coating, the power for RF sputtering of HfO2 is 40 - 100 W, the power for DC sputtering of WS2 is 150 W, and the sputtering time is 90 - 100 minutes.
Citation Information
Cited By
WS2-based composite coating and preparation method thereof
CN122105314A